A atuação do Iphan - GO na promoção de ações em educação patrimonial (2009-2021) - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This work aims to present a survey and analysis of heritage education actions developed by the Instituto do Patrimônio Histórico e Artístico Nacional (Iphan) in Goiás, especially between the years 2009 to 2021. This period comprises the establishment of one of the institutional landmarks of Heritage Education at Iphan: the implementation of Casas do Patrimônio1, currently designated as Redes do Patrimônio2. The origin of this project dates to 2007 from internal discussions at Iphan with the purpose of expanding the institutional capillarity of this institution, as well as connecting environments that carry out practices and activities of an educational nature that have as principle the valorization of cultural heritage. The project, therefore, is based on the institute's demand to consolidate, from a transversal and dialogic perception, new ways of relating to civil society and local authorities. Thus, in addition to presenting a history of heritage education actions, the projects developed within the scope of the state superintendence of Goiás, aimed at the preservation of the cultural heritage of the State, were analyzed. The State of Goiás has three Heritage Houses: one in Goiânia, one in Pirenópolis and a third in the Cidade de Goiás. In fact, the study made it possible to identify the growth in the number of educational actions carried out from 2009 onwards, in accordance with the implementation of the first officially recognized Casas do Patrimônio. The actions from then on maintained some patterns observed previously, although having a greater appeal to diversity. To this end, methodologically, interviews, mapping, data collection and document analysis were used. The results obtained with the research were systematized and with them a book was prepared in the E-Book format containing, in addition to this information, discussions that intend to produce reflections in the readers.
Keywords: Educação patrimonial; Iphan; Casas do Patrimônio; Goiás, GO; Heritage education; CIENCIAS HUMANAS::HISTORIA